Morphological Characterization of Giant Mottled Eel (Anguilla marmorata) Gastrointestinal Tract that Origin from Thua Thien Hue, Vietnam - Huyen, Kieu Thi; Linh, Nguyen Quang (Research Aspects in Agriculture and Veterinary Science Vol. 2, 2021)
This study investigated the dietary component and morphology of the digestive tract of Anguilla marmorata during its yellow stages (non-migrants). Anguilla marmorata is also widely distributed, exploited and cultivated with high economic value. A total of 127 samples, ranging in total length from 17-108 cm and weight from 10-3200 g were collected from Thua Thien Hue, Vietnam. The structure of the gastrointestinal tract indicated that Anguilla marmorata has the typical characters of carnivorous fish such as a wide mouth, small teeth in bands; free tongue; short esophagus, stomach, and intestines made up of folds. The mouth size of Anguilla marmorata ranged from 1.81-6.6 cm and it increased with the body weight of fish. Anguilla marmorata is an animal-eating species with an RLG (relative length of the gut) ranging from 0.34 to 0.41 (RLG <1). Crustacea is the preferred food of eels with the highest proportion of the number, weight, and frequency of crustaceans in the gastrointestinal tract with 65%, 64%, and 80%, respectively. Crustacea was also the most important food of Anguilla marmorata in the wild with the index of relative importance (IRI%)=79%. Correlation equation between length (L=17-108 cm) and weight (W=10-3200 g) of Anguilla marmorata is L=9.948W0.0622 with correlation coefficient R2=0.93. Our report provides new dietary information about A. marmorata that is useful in nutrition planning and aquaculture potential.